2016
DOI: 10.1080/00140139.2016.1237676
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar contribution to the trunk forward bending and backward return; age-related differences

Abstract: Age-related differences in lumbar contribution to the trunk motion in the sagittal plane were investigated. Sixty individuals between 20-70 years old in five gender-balanced age groups performed forward bending and backward return with slow and fast paces. Individuals older than 50 years old, irrespective of the gender or pace, had smaller lumbar contribution than those younger than this age. The lumbar contribution to trunk motion was also smaller in female participants than male participants, and under fast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Vazirian et al . 11 studied the differences in the lumbar contribution in four quartiles of forward bending and backward return between five age groups spanning from 20 to 70 years old. The investigators reported a smaller lumbar contribution in the groups older than 50 years, in the males and females, as well as a smaller lumbar contribution in females versus males in all of the quarters of forward bending and backward return.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vazirian et al . 11 studied the differences in the lumbar contribution in four quartiles of forward bending and backward return between five age groups spanning from 20 to 70 years old. The investigators reported a smaller lumbar contribution in the groups older than 50 years, in the males and females, as well as a smaller lumbar contribution in females versus males in all of the quarters of forward bending and backward return.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, references of each identified study were also investigated for identification of any study that was missed in the database search. Finally, a recent study by the authors 11 which meets the review inclusion criteria was added to the list of included studies (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Data for 19 asymptomatic female controls (aged 40–70 years old) were extracted from an earlier study (Vazirian et al, 2016a). All participants completed an informed consent procedure approved by the University of Kentucky Institutional Review Board before participation.…”
Section: Methodsmentioning
confidence: 99%
“…Age, stature, body mass, and body mass index (BMI) for the two groups were comparable (Table.1). Asymptomatic controls with any history of LBP or musculoskeletal disorders were excluded (Shojaei et al, 2016; Vazirian et al, 2016a). Patients with acute LBP were excluded if they had any significant cognitive impairment, intention to harm themselves or others, or substance abuse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation